EVALUASI KETERAMPILAN BERBICARA BAHASA ARAB SISWA MADRASAH ALIYAH DI PROVINSI JAMBI - Sanjaya, Budi; Hidayat, Wahyu (Arabi : Journal of Arabic Studies, 2021)
This study aims to describe the perceptions of teachers and students about speaking skills in self-assessment, learning approaches and forms of learning Arabic. This study has distributed questionnaires to 51 teachers of Arabic Language Subjects and 395 students of MAN in Jambi Province and made observations to 8 Arabic teachers. Data were analyzed descriptively, namely frequency, percentage, average and standard deviation using SPSS version 25. Qualitative data were analyzed qualitatively descriptively. The results showed that the teacher's self-assessment in speaking skills was at a high level and students' self-assessment in speaking skills was at a moderate level. The speaking skills learning approach from the teacher's perceptions is at a sufficient level and the speaking skills learning approach from the students' perceptions shows it is at a moderate level. The form of learning MPBA speaking skills from teacher perceptions is at a high level. Likewise, the form of learning speaking skills from students' perceptions is high.